Mental health service users' experiences of diabetes care by Mental Health Nurses: an exploratory study. Issue 8 (18th February 2014) - Nash, M.
<x xml:space="preserve">Abstract</x> Accessible summary Little is known about mental health service users' experiences of physical conditions such as diabetes. Stigma and diagnostic overshadowing occurred when seeking help with physical problems. A split in mental and physical health left two distinct illness identities – the mental health service user who is largely ignored in primary care and the diabetic who is largely ignored in mental health. Most participants mentioned experiencing physical complications of diabetes. Abstract This paper is a report of a study exploring mental health service users' (MHSUs') experiences of diabetes care. Diabetes is a growing clinical concern in mental health nursing practice. However, little is known about MHSUs' experience of diabetes care. This is a descriptive qualitative study. Semi‐structured telephone interviews were held between June and October 2011, with seven MHSUs who had diabetes. Participants reported experiences of stigma and diagnostic overshadowing (DO) when reporting symptoms of diabetes or when feeling unwell. Participants also encountered a split between their mental health and diabetes care needs, which resulted in a lack of holistic or integrated care. All participants mentioned experiencing complications of diabetes even to the extent of diabetic ketoacidosis. Mental health nurses (MHNs) must critically reflect on their attitudes towards service users that report physical symptoms to ensure that stigma and DO do not constitute barriers to appropriate screening and treatment. The complex relationship that exists between mental illness and diabetes requires MHNs to ensure physical and mental health care are wholly integrated and not split. Education needs are apparent so that symptoms and complications can be recognized and treated accordingly.